Where on earth? - Abramson, Helen; Houston, Rob; Setford, Steve; Skene, Rona; DK Publishing, Inc (New York DK Pub, 2013)
"Contains a collection of 80 ... specially commissioned world maps that show you where everything is on our planet. The world's most dangerous predators, ancient mummies, disastrous asteroid impacts, and towering skyscrapers--find out where they all are in this ultimate atlas that showcases the best of geography, history, nature, culture, and technology"--Flap p. [1] of dust jacket
Land, sea, and air -- Living world -- People and planet -- Engineering and technology -- History -- Culture
"Geography as you've never seen it before"--P. [1] of cover
Atlases
Includes index
Maps on endpapers
Relief shown by shading and gradient tints
13
Keywords: Atlases; Atlases; Children's atlases; Geography -- Juvenile literature; Geography; World atlases